Modelling and interpreting the impact of policy and price scenarios on farm-household sustainability: Farming systems vs. result-driven clustering - Viaggi, D.; Raggi, M.; Gomez y Paloma, S. (Environmental modelling & software : with environment data news, 2013)
The Common Agricultural Policy of the European Union is subject to a continuous process of reform. The objective of this paper is to evaluate the effect of decoupling and related policy and market scenarios, as introduced in the 2003 CAP reform, by way of selected agriculture sustainability indicators and through the aggregation of individual farm-household simulated behaviour. The approach is based on the use of a Net Present Value-maximising dynamic farm-household model. The model is implemented on 80 farm-households to simulate the reaction to scenarios of different agricultural systems in 8 EU countries. The results are measured through three main indicators – represented by farm income, labour use and nitrogen use – evaluated over a period of 14 years. The results of individual farm-households are aggregated first using the concept of farming system and then based on a cluster analysis using the results in different scenarios as discriminant variables. The results show that the CAP as a whole is crucial for the sustainability of farming systems in terms of income and employment, but also provides incentives for higher use of inputs, suggesting a trade-off between social and environmental sustainability concerns. In the range of variation considered, nitrogen and labour use appear much more reactive than income and indicate much higher variability across farms and scenarios. The aggregation by agricultural system denotes rather different behaviour among systems. However, the cluster analysis shows that results appear to be better interpreted by patterns of individual characteristics (location in the plain, structure, asset endowment, labour, etc.) than by country, specialisation or technology. ► The CAP is crucial for the sustainability of farming systems. ► But also provides incentives for higher use of inputs. ► Nitrogen and labour use are the parameters more reactive to scenarios. ► Results are better explained by patterns of individual characteristics.